Assessing Mutations in Treatment Response-related Genes in Egyptian Patients with Non-small Cell Lung Cancer - Anan Omar; Abeer Bahnassy; Rabab Gaafer; Eman El Desouky; Amina Mohamed Medhat (Asian Pacific Journal of Cancer Biology, 2022)
Background: Epidermal growth factor receptor (EGFR) and Kirsten rat sarcoma viral oncogene homolog (K-RAS) are the most common driver genes in patients with non-small cell lung cancer adenocarcinomas (NSCLC/ADC), which affects treatment. Therefore, this study determines the frequency and patterns of EGFR and K-RAS mutations in Egyptian patients with NSCLC/ADC and correlates them with clinicopathological features. Methods: A retrospective analysis of 139 patients diagnosed with NSCLC/ADC and screened for EGFR and K-RAS mutations was conducted; further evaluating clinicopathological characteristics and mutational status. Results: This study included 101 males and 38 females with a median age of 57.7 ± 10.5 years. EGFR mutations were detected in 22.3% (12.2% in exon 19, 8.6% in exon 21, and 1.4% in exon 18) and K-RAS mutations in 17.3% (15.8% in codon 12 and 1.4% in codon 13), whereas combined mutations were detected in nine patients (6.5%). Furthermore, EGFR mutations were non-significantly more common in females and nonsmokers, contradicting K-RAS mutations, which were more common in males and smokers. Conclusion: EGFR and K-RAS mutations are common in Egyptian patients with NSCLC/ADC (National Cancer Institute experience). Their incidences were between the Asian Pacific and Europeans. Also, their mutations led to dysregulation in tyrosine kinase activity, which correlates with the late disease stage and poor progression. Therefore, analyzing them should be done to determine a better treatment method and predict survival outcomes.